Teachers’ implementation of scientific approach in teaching English for Senior high school students - Halawatil Iman; Sofyan Abdul Gani; Bustami Usman (Universitas Syiah Kuala, 2021)
The scientific approach constitutes an approach to Indonesia's 2013 curriculum. Since it is imperative for Indonesian education, all teachers need to understand, manage, and apply it in the teaching-learning process. Unfortunately, many English teachers still use inappropriate methods as in the 2013 curriculum. This qualitative research aims at discovering the implementation of a scientific approach by English teachers at State Senior High School in Lhokseumawe. The objects were English teachers at SMAN 1 Lhokseumawe, SMAN 2 Lhokseumawe, and SMAN 5 Lhokseumawe. The tools used in this study were observation for three high school English teachers in the schools. The observation results toward the implementation of five scientific approach stages exposed that the English teachers did not carry out the five stages completely. The teacher should master, understand, and apply the teaching process by following the whole stages of the scientific approach. Class mastery and time management are vital for the learning process. Thus, the teachers should consider those points. Hence, interesting supporting media, appropriate learning material, and methods must be considered by the teachers in teaching so that the students will be motivated to learn.